Nyquist WDM superchannel using offset-16QAM and receiver-side digital spectral shaping - Xiang, Meng (2014)
The performance of Nyquist WDM superchannel using advanced modulation formats with coherent detection is degraded due to the existence of both inter-symbol interference (ISI) and inter-channel interference (ICI). Here, we propose and numerically investigate a Nyquist WDM superchannel using offset-16QAM and receiver-side digital spectral shaping (RS-DSS), achieving a spectral efficiency up to 7.44 bit/s/Hz with 7% hard-decision forward error correction (HD-FEC) overhead. Compared with Nyquist WDM superchannel using 16QAM and RS-DSS, the proposed system has 1.4 dB improvement of required OSNR at BER = 10−3 in the case of back-to-back (B2B) transmission. Furthermore, the range of launched optical power allowed beyond HD-FEC threshold is drastically increased from −6 dBm to 1.2 dBm, after 960 km SSMF transmission with EDFA-only. In particular, no more than 1.8 dB required OSNR penalty at BER = 10−3 is achieved for the proposed system even with the phase difference between channels varying from 0 to 360 degree.